1995
DOI: 10.1063/1.358791
|View full text |Cite
|
Sign up to set email alerts
|

Field enhancement of the photoelectric and secondary electron emission from CsI

Abstract: We have measured the electron emission from a CsI-coated multiwire cathode, induced by ultraviolet photons and electrons, in vacuum at high electric fields. We found an enhancement in quantum efficiency of a factor of 1.5 at 160 nm, 3 at 185 nm, and 25 above 200 nm, at a field of 500 kV/cm. At the short wavelengths the amplitude of the effect is a linear function of the square root of the field strength. The enhancement of the electron-induced secondary electron emission yield is dependent on the primary elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
2
22
1
Order By: Relevance
“…nm CsI films are found to be about 5.30 eV, 5.25 eV, 5.00 eV and 5.20 eV respectively. The observed discrepancy with and Buzulutskovet al [41] data (Eg∼ 5.9 eV) may be due to the heat-enhanced CsI film compared to "as-deposited"…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…nm CsI films are found to be about 5.30 eV, 5.25 eV, 5.00 eV and 5.20 eV respectively. The observed discrepancy with and Buzulutskovet al [41] data (Eg∼ 5.9 eV) may be due to the heat-enhanced CsI film compared to "as-deposited"…”
Section: Resultscontrasting
confidence: 59%
“…We have found that the band gap energies of 500 nm, 300 nm, 50 nm and 30 nm CsI films are about 5.30 eV, 5.25 eV, 5.00 eV and 5.20 eV respectively. A. Buzulutskov et al [41] have also derived the band gap energy to be 5.90 eV from experimental QE dependence on wavelength. The high band gap energy obtained by A. Buzulutskov et al [41] may be due to the heat treatment of CsI film compared to "as-deposited" films in our case.…”
Section: Optical Properties Of Csi Thin Filmsmentioning
confidence: 99%
“…The value of photon energy (hν) extrapolated to α = 0 gives an absorption edge which corresponds to the optical band gap energy E g . The extrapolation gives an optical band gap energy E g ≈ 5.43 eV, which can be compared with the band gap energy E g ≈ 5.9 eV derived from experimental QE dependence on wavelength [10] for heat enhanced CsI thick films.…”
Section: Optical Properties Of 500 Nm Thick Csi Filmmentioning
confidence: 99%
“…The CsI/Si sample showed a slight increase throughout the range of bias voltages, which is consistent with the results reported previously. 9 On the other hand, the relative QE of the CsI/ MgO/MWCNTs/Si sample increased significantly with increasing bias voltage, occasionally exceeding 10 000 ͑data not shown here͒. The high value in the graph, approximately 2000 at a bias voltage of approximately Ϫ160 V, suggests that a single photon can generate as many as 500 electrons when a plausible absolute QE ͑147 nm͒ of 0.25 is used for CsI.…”
Section: Evaluation Of a Cesium Iodide Photocathode Assisted With Mgomentioning
confidence: 90%